Evidential base for lack of association between preventive vaccination and autism spectrum disorders (Literature review) - S. V. Grechanyy; V. V. Pozdnyak; Yu. V. Khutoryanskaya; О. S. Kul’bakh; G. О. Bagaturiya (Журнал инфектологии, 2020)
The etiology of autism spectrum disorders still remains unclear. Recently a number of research have emerged linking the increment of vaccination in population and the increased frequency of autism spectrum disorders. In this review we analyzed the most representational studies on this issue. The main hypotheses linking autism spectrum disorders and vaccination were identified: association of vaccination against measles and enteropathy caused by the components of the measles virus vaccine strain which indirectly affects the brain; the onset of autism symptoms as a result of postvaccine encephalitis due to the use of various vaccines: the Measles, Mumps, Rubella vaccine, Diphtheria, Pertussis, Tetanus vaccine; the effect of multivaccine on the development of autism spectrum disorders; the effect of individual components of vaccines, particularly thimerosal, on the development of childhood autism and similar conditions. The data of epidemiological studies that refute these hypotheses were presented. Large samples in these studies provide a level of statistical significance sufficient enough to reveal even rare statistical associations. These results actually disproved the notion that vaccines cause autism.